School-based peer education intervention on physical activity in Iranian adolescent girls: an application of the theory of planned behavior - Ranaei, Afsaneh; Tavakoly Sany, Seyedeh Belin; Vahedian Shahroodi, Mohammad; Sabahi, Azam; Tehrani, Hadi; Khajavi, Abdoljavad (Frontiers in Public Health, 2025)
IntroductionThe level of physical activity (PA) among Iranian adolescent girls is significantly lower than the recommended level. This survey aims to examine the impact of school-based peer education Intervention on promoting PA using the theory of planned behavior (TPB) among girls in high school.MethodsA quasi-experimental study was conducted on 160 girls in high school of Gonabad, Iran. School-based peer education program was conducted for the intervention group through five training sessions and the three-month follow-up to enhance clarity. Data was collected using a researcher-made questionnaire based on TPB, the International Physical Activity Questionnaire (IPAQ), and demographic information. The content validity Index, content validity ratio, and Cronbach’s alpha coefficient values demonstrated strong content validity and reliability (> 0.85). The obtained data were analyzed using appropriate statistical tests using SPSS software 20.ResultsThe average age of the participants was 13.5 ± 1.2 years, and 65% had low levels of PA. The intervention group demonstrated significant improvements across all constructs of the TPB compared to the control group. The mean scores for attitude toward behavior (p = 0.012), subjective norms (p = 0.023), perceived behavioral control (p = 0.003), and behavioral intention (p = 0.001) showed significant enhancement in the intervention group. Additionally, physical activity behavior improved significantly (p < 0.05) after the intervention, while no significant improvement was observed in the control group (p > 0.05). The Cohen’s d values for all constructs in the intervention group, except for subjective norms, exceeded 0.8, indicating a large effect size for these constructs.ConclusionSchool-based peer education using the TPB can be used as an effective theory to promote the level of PA among high school girls. This approach strengthens attitudes, perceived behavioral control, and subjective norms, leading to improved behavioral intentions and increased PA among female students.